(untitled) (Iranian Journal of Kidney Diseases, 2021)
Introduction. Pulmonary artery hypertension (PAH) is common in end stage renal disease (ESRD) patients undergoing hemodialysis. Fibroblast growth factor-23 (FGF-23) increases in hemodialysis but its relationship with PAH is not completely understood. The aim of this study was to evaluate the relation between FGF-23 level and development of PAH in ESRD patients undergoing hemodialysis. Methods. Patients undergoing hemodialysis for more than 6 months were enrolled in this cross-sectional study. Transthoracic echocardiography was performed to measure ejection fraction and pulmonary artery pressure (PAP) in all patients. Patients were grouped into normal PAP (PAP < 25 mmHg), elevated PAP (25 < PAP < 35 mmHg) and PAH (PAP > 35 mmHg). Parathormone hormone, calcium, phosphorus, vitamin D, and hemoglobin levels were also evaluated. Results. Eighty-five patients (48 male, 56.47%) enrolled in this study. The mean age of the patients was 51.05 ± 16.45 years. Most of the patients (49, 57.65%) had normal PAP, 20 (23.53%) had elevated PAP and 16 (18.82%) had PAH. Serum biochemical markers and demographic characteristics were not significantly related to different PAP values (P > .05). Most of the patients (42, 49.41%) had normal FGF-23 levels. There was a significant relationship between PAP groups and FGF-23 and parathormone levels, P < .001, and P < .05; respectively. FGF-23 was significantly higher in PAH and elevated PAP groups compared with normal PAP group (P < .05). Only a significant positive correlation was observed between FGF-23 levels and PAP (P < .001). Conclusion. This finding highlights the possible role of FGF-23 in the development of vascular complications in ESRD patients. DOI: 10.52547/ijkd.5940